2011
DOI: 10.1002/jsfa.4479
|View full text |Cite
|
Sign up to set email alerts
|

One-step multiplex PCR method for the determination of pecan and Brazil nut allergens in food products

Abstract: The presented multiplex PCR method is specific enough and can be used as a fast approach for the detection of major allergens of pecan or Brazil nuts in food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The sensitivity of our multiplex PCR assay was comparable with allergen reported previously. Hubalkova and Rencova (2011) reported detection limits of 100 pg for pecan and Brazil nut allergy. Zhang et al (2018) reported detection limits of 10-100 pg for peanut, soybean and sesame allergy.…”
Section: Specificity and Sensitivity Test Of The Multiplex Pcr Assaymentioning
confidence: 99%
“…The sensitivity of our multiplex PCR assay was comparable with allergen reported previously. Hubalkova and Rencova (2011) reported detection limits of 100 pg for pecan and Brazil nut allergy. Zhang et al (2018) reported detection limits of 10-100 pg for peanut, soybean and sesame allergy.…”
Section: Specificity and Sensitivity Test Of The Multiplex Pcr Assaymentioning
confidence: 99%
“…These conditions are dangerous if the contaminant taxon is toxic or allergenic for humans. A typical example is that of nuts and almonds which cause allergies in many people [91]. Several commercial foodstuffs (e.g., bakery, pastry, and snacks) showed contamination by these plants (see, e.g., [76,92]).…”
Section: Honeymentioning
confidence: 99%